ENT 530 Social Media Portfolio: Nutella Nutball Cookie By Faiz / Muhammad Faiz Mohamad Zainuddin - Mohamad Zainuddin, Muhammad Faiz (2021)
The content of this report is a portfolio of a business named NUTELLA NUTBALL COOKIE BY FAIZ and how the business utilises Facebook as its main platform to promote its products to the end consumer. NUTELLA NUTBALL COOKIE BY FAIZ is a business that have been registered in the e-Commerce domain, which sells Nutella nutball cookie as their product. The business established since April 2021 in Ranau, Sabah with the goal of to provide great satisfaction to their customers and clients with everyday fresh baked cookies. The current bakery product trend such as cookies offered by numerous of bakers are usually bad in textures and inconsistent in their flavours, quality, textures, and taste. NUTELLA NUTBALL COOKIE BY FAIZ saw this as an opportunity to provide something fresher cookie as well as consistent in terms of flavours, quality, textures, and taste with our everyday baked Nutella nutball cookies. We are able to provide new flavour cookie as well that still rare in the market which is the combination of Nutella and almond nuts in the cookie ingredients. Hence, Nutella nutball cookie as our main product. As mentioned earlier, NUTELLA NUTBALL COOKIE BY FAIZ utilises Facebook as their main platform to promote its business. In our official Facebook page, we develop and use three main ways of posting and copywriting on the Facebook page which is, teaser posts, soft sell posts, as well as hard sell posts. Teaser post are post that only reveal few and little information about any products, promotions, or collaboration on the business. Mainly in our business, teaser posts are used to exposed to the end consumer about our product launching to increase its hype before it is officially launched and available for sale. Soft sell posts are subtle advertisements that remind the end consumer that our product exist and give awareness about the product sold. On the contrary, hard sell posts are more aggressive posts to sell our products and usually it will take an immediate action for the end consumer to buy the product. Eventually, NUTELLA NUTBALL COOKIE BY FAIZ had started off quite competent since its first established on April 2021 and are planning to expand more both in short term and long term. In a short term, we plan to expand our product offered which will be more variety in the future. We hope for research and development activities before proceeding into new product generation. Meanwhile, in a long term we hope that we can be an established business among the local bakery product business in Malaysia.